Failure to rescue following anatomical lung resection. Analysis of a prospective nationwide database - Gómez-Hernández, María Teresa; Rivas, Cristina; Novoa, Nuria; Jiménez, Marcelo F.; , the Spanish Group of Video-assisted Thoracic Surgery (GEVATS) (Frontiers in Surgery, 2023)
BACKGROUND: Rescue failure has been described as an important factor that conditions postoperative mortality after surgical interventions. The objective of this study is to determine the incidence and main determinants of failure to rescue after anatomical lung resections. METHODS: Prospective multicenter study that included all patients undergoing anatomical pulmonary resection between December 2016 and March 2018 and registered in the Spanish nationwide database GEVATS . Postoperative complications were classified as minor (grades I and II) and major (grades IIIa to V) according to the Clavien-Dindo standardized classification. Patients that died after a major complication were considered rescue failure. A stepwise logistic regression model was created to identify predictors of failure to rescue. RESULTS: 3533 patients were analyzed. In total, 361 cases (10.2%) had major complications, of which 59 (16.3%) could not be rescued. The variables associated with rescue failure were: ppoDLCO% (OR, 0.98; 95% CI, 0.96-1; p=0.067), cardiac comorbidity (OR, 2.1; 95% CI, 1.1-4; p=0.024), extended resection (OR, 2.26; 95% CI, 0.94-5.41; p=0.067), pneumonectomy (OR, 2.53; 95 CI, 1.07-6.03; p=0.036) and hospital volume <120 cases per year (OR, 2.53; CI 95%, 1.26-5.07; p=0.009). The area under the curve of the ROC curve was 0.72 (95% CI: 0.64–0.79). CONCLUSION: A significant percentage of patients who presented major complications after anatomical lung resection did not survive to discharge. Pneumonectomy and annual surgical volume are the risk factors most closely related to rescue failure. Complex thoracic surgical pathology should be concentrated in high-volume centers to obtain the best results in potentially high-risk patients.